Maternal care by Early Cretaceous cockroaches. (4th March 2019) - Gao, Taiping; Shih, Chungkun; Labandeira, Conrad C.; Liu, Xin; Wang, Zongqing; Che, Yanli; Yin, Xiangchu; Ren, Dong
Abstract : Most cockroaches produce a special capsular structure, the ootheca, to enclose eggs for protection and maternal brood care. However, the origin and early evolution of the cockroach ootheca is poorly known, attributable to a lack of fossil evidence from the Mesozoic. Here, we report the earliest known cockroach fossil possessing an internally partitioned ootheca: Piniblattella yixianensis Gao, Shih & Ren sp. nov. is described from the mid Early Cretaceous Yixian Formation of China. The ootheca of this species measures 46–62% of its body length, contains 60–70 eggs, and exhibits the oviparity B reproduction mode, similar to that of the extant ectobiid and blattid cockroaches. In conjunction with several isolated ootheca specimens preserved in the mid-Cretaceous Myanmar amber (Burmite), we infer that the cockroach reproductive mode using the complete oothecate structure occurred during or before the mid Early Cretaceous. Maternal care associated with the oothecate condition in these Cretaceous cockroaches added a unique and major life-history trait, later resulting in true viviparity. This new life-history trait providing maternal protection and care may have been a key factor in the subsequent evolutionary diversification and ecological expansion of modern cockroach lineages. http://zoobank.org/urn:lsid:zoobank.org:pub:588C91F4-FB8D-43E5-8C2D-86D50393B851